RADDOSE-XFEL: femtosecond time-resolved dose estimates for macromolecular XFEL experiments - Dickerson, JL; McCubbin, PTN; Garman, EF (International Union of Crystallography, 2020)
For macromolecular structure determination at synchrotron sources, radiation damage remains a major limiting factor. Estimation of the absorbed dose (J kg−1) during data collection at these sources by programs such as RADDOSE‐3D has allowed direct comparison of radiation damage between experiments carried out with different samples and beam parameters. This has enabled prediction of roughly when radiation damage will manifest so it can potentially be avoided. X‐ray free‐electron lasers (XFELs), which produce intense X‐ray pulses only a few femtoseconds in duration, can be used to generate diffraction patterns before most of the radiation damage processes have occurred and hence hypothetically they enable the determination of damage‐free atomic resolution structures. In spite of this, several experimental and theoretical studies have suggested that structures from XFELs are not always free of radiation damage. There are currently no freely available programs designed to calculate the dose absorbed during XFEL data collection. This article presents an extension to RADDOSE‐3D called RADDOSE‐XFEL, which calculates the time‐resolved dose during XFEL experiments. It is anticipated that RADDOSE‐XFEL could be used to facilitate the study of radiation damage at XFELs and ultimately be used prior to data collection so that experimenters can plan their experiments to avoid radiation damage manifesting in their structures.